Effect of nifedipine with and without sildenafil citrate for the management of preterm labor in pregnant women: A randomized clinical trial - Shahla Nasrolahei; Seyedeh Arezoo Hoseini; Seyedeh Azadeh Hosseini; Seyedeh Narjes Khatoon Hosseini; Seyedeh Sahar Hosseini; Parsa Moradian Lotfi (Shahid Sadoughi University of Medical Sciences, 2023)
Abstract Background: Preterm labor is one of the main causes of neonatal mortality and its treatment is still challenging. Objective: The study aimed to compare the effectiveness of nifedipine (Nif) with and without sildenafil citrate (SC) for the treatment of preterm labor in pregnant women. Materials and Methods: In this clinical trial study, 126 pregnant women referred to the Fatemieh hospital, Hamadan, Iran with a complaint of preterm labor were evaluated. Participants were randomly divided into 2 groups of Nif 20 mg orally (single dose), then 10 mg every 6-hr, and at the same time vaginal SC 25 mg every 8 hr (Nif + SC) or Nif alone. Treatment was continued for 48-72 hr if uterine contractions did not resolve in both groups. Delivery rates at the time of hospitalization and neonatal outcome were compared between the 2 groups. Results: No statistically significant difference was observed between the 2 study groups in terms of mean age, gestational age, body mass index, and parity. 76.2% of Nif + SC participants in the first 72 hr of hospitalization and 57.2% of Nif participants remained without delivery (p = 0.02). The neonatal hospitalization rate of the Nif + SC group in the neonatal intensive care unit was 25.4% and in the Nif group was 42.9% (p = 0.03). Conclusion: Nif with SC is superior to Nif alone in women at risk of preterm labor due to increasing gestational age and better neonatal outcomes.